Peripheral chemoreceptors sustain central chemoreflex potentiation and cardiorespiratory abnormalities in high-output heart failure - Ortiz-Cisternas, F (SPRINGER HEIDELBERG, 2026)
Central chemoreflex activation worsens cardiorespiratory dysfunction in high-output heart failure (HO-HF). Recently, interdependence between both peripheral and central chemoreceptors has been linked to alterations in cardiorespiratory regulation. Whether central chemoreflex potentiation in HO-HF requires sensory inputs from peripheral chemoreceptors remains completely unknown. Accordingly, we hypothesized that peripheral-central chemoreceptor interaction promotes cardiorespiratory dysfunction in non-ischemic HO-HF. We used male Sprague-Dawley rats to investigate the role of carotid bodies (CBs), the main peripheral chemoreceptors, on autonomic, respiratory, and cardiac function alterations during the progression of HO-HF. CB denervation (CBD) was used to eliminate CB inputs in HO-HF rats. The effect of CBD on HO-HF related cardiac, autonomic, and ventilatory function was measured using echocardiography, pressure-volume loop analysis, electrocardiography, plethysmography, and telemetry. HO-HF rats exhibited enhanced central chemoreflex drive, irregular breathing, autonomic imbalance, cardiac electrophysiological abnormalities, cardiac diastolic dysfunction, and cardiac hypertrophy. Remarkably, CBD completely normalized central chemoreflex function in HO-HF rats, restored ventilatory stability, reduced apnea-hypopnea incidence, improved heart rate variability, shortened QRS and PR intervals, attenuated collagen deposition, and ameliorated diastolic dysfunction. Additionally, CBD also corrected respiratory-cardiovascular coupling abnormalities in HO-HF rats. These findings demonstrate that an intact and functional CB is necessary for the development of cardiorespiratory disturbances in non-ischemic HO-HF. Targeting CB-central chemoreceptor interdependence may represent a novel therapeutic approach for non-ischemic HO-HF.